Analisis Kinerja Penyuluh Terhadap Pelaksanaan Tugas Pokok Penyuluh Pertanian di Desa Limapoccoe Kecamatan Cenrana Kabupaten Maros - Herman Herman; Arifin Arifin; Abd. Asis Pata (Jurnal Agribis, 2022)
This study aims to analyze the performance of agricultural extension workers in Limampoccoe Village. The research was conducted in Limampoccoe Village, Cenrana District, Maros Regency. The research method used in this research is the survey method. The data method used is observation and interviews with questionnaires as a data collection tool. The data used is primary data, namely data obtained directly from the field using a questionnaire as a data collection tool and secondary data is data obtained from the relevant agencies in this study. Based on the results of the research on Agricultural Extension Performance Analysis in Limampoccoe Village, Cenrana District, Maros Regency, it was 77.33%, this picture shows that in general Agricultural Extension in Limampoccoe Village is in the high category. categorize good.